The Effect of Family Business Exposure on Entrepreneurial Intention Through Coercive, Normative, Mimetic Pressure: A Study on the Second Generation of Family Business Successors in Jombang, Indonesia - Aisy, Rafida (Manunggal Halim Jaya, 2025)
This research examines the influence of family business exposure on entrepreneurial intention through coercive, normative, and mimetic pressure. The variables used in the study are family business exposure, entrepreneurial intention, coercive pressure, normative pressure, and mimetic pressure. The population in this study is second-generation business actors who continue the family business in Jombang. The sampling technique used was purposive sampling. Questionnaires were distributed via Google Forms to respondents who were second-generation entrepreneurs who had continued their family business in Jombang. This research obtained 140 samples, and 138 samples were suitable for analysis. Data were analyzed with Smart PLS software and using path analysis. The research results show that family business exposure influences entrepreneurial intention through coercive, normative, and mimetic pressure on second-generation business actors who continue the family business in Jombang.